2018
DOI: 10.1002/ajim.22891
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of cancer risks for firefighters, police, and armed forces among men in a Canadian census cohort

Abstract: Canadian firefighters, police, and armed services, may be at an increased risk of developing certain cancers. Results suggested that a healthy worker effect may influence risk estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 36 publications
8
38
3
Order By: Relevance
“…Since firefighters need to pass regular medical check-ups throughout their employment it cannot be ruled out that skin cancer has been more easily detected among firefighters than in the general population, although the check-ups do not specifically include cancer screening. Our finding that firefighters with long work duration have an increased risk of prostate cancer is in line with findings from several studies which found that firefighters have an increased risk of prostate cancer or that prostate cancer risk is associated with longer service (Glass et al 2016;Harris et al 2018;LeMasters et al 2006;Petersen et al 2018a;Jalilian et al 2019). A review and meta-analysis on prostate cancer among firefighters showed small, but statistically significant excesses (Sritharan et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Since firefighters need to pass regular medical check-ups throughout their employment it cannot be ruled out that skin cancer has been more easily detected among firefighters than in the general population, although the check-ups do not specifically include cancer screening. Our finding that firefighters with long work duration have an increased risk of prostate cancer is in line with findings from several studies which found that firefighters have an increased risk of prostate cancer or that prostate cancer risk is associated with longer service (Glass et al 2016;Harris et al 2018;LeMasters et al 2006;Petersen et al 2018a;Jalilian et al 2019). A review and meta-analysis on prostate cancer among firefighters showed small, but statistically significant excesses (Sritharan et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In 2007, an International Agency for Research on Cancer (IARC) working group reported elevated summary relative risk estimates for testicular cancer, prostate cancer and non-Hodgkin's lymphoma (NHL) in a meta-analysis of cancer in firefighters and concluded, based on limited evidence, that occupational exposure as a firefighter is possibly carcinogenic to humans (ie, categorised as Group 2B) 1. The literature includes several studies published since the IARC monograph 2–16. Nevertheless, findings still differ among specific cancer sites; perhaps from heterogeneity in exposures, work practices, personal protective equipment use or simply from chance alone 17…”
Section: Introductionmentioning
confidence: 99%
“…The WTC combined Rescue/Recovery cohort includes firefighters, law enforcement and construction workers. An increased risk of melanoma has consistently been reported in previous studies of firefighters (Casjens et al, 2020) and police officers (Finkelstein, 1998, Forastiere et al, 1994, Harris et al, 2018, while results of studies of construction workers are mainly negative (Alicandro et al, 2020, Gallagher et al, 1987, Hakansson et al, 2001, Robinson et al, 1995. Workplace exposure to UV radiation has been suggested to explain these findings, since other occupational groups with opportunity of UV exposure, such as offshore workers (Stenehjem et al, 2017), airline pilots and cabin crews (Sanlorenzo et al, 2015), and agricultural workers (Kachuri et al, 2017) also experience an increased incidence of melanoma.…”
mentioning
confidence: 83%